Paths of discovery: the life and achievements of Ronald Andrew Asherson, on the occasion of his 90th birthday - E. A. Sborshchikova; A. V. Vorobev (Акушерство, гинекология и репродукция)
In December 19, 2024, there was the 90th anniversary of the birth of Ronald Andrew Asherson, a great scientist who prominently contributed to the development of medicine. His work in the field of clinical immunology, especially in the study of catastrophic antiphospholipid syndrome (CAPS), has become the basis for modern approaches to the diagnostics and treatment of this rare but dangerous disease. Asherson's discoveries notably widened the understanding of the mechanisms behind autoimmune disorders associated with phospholipids and improved the prognosis of CAPS patients. Asherson was not only the discoverer in studying CAPS, but also influenced a whole generation of scientists and clinicians. It is a great importance to preserve the memory about his life and scientific achievements for future generations of researchers and doctors who will continue to develop and use his ideas in practice.